The eating motivations scale (EATMOT): Development and validation by means of confirmatory factor analysis (CFA) and structural equation modelling (SEM) - Guiné Raquel P. F.; Duarte João; Ferrão Ana Cristina; Ferreira Manuela; Correia Paula; Cardoso Ana Paula; Bartkiene Elena; Szűcs Viktória; Nemes Levente; Ljubičić Marija; Černelič-Bizjak Maša; Isoldi Kathy; et al. (Sciendo, 2020)
The objective was to develop and validate an instrument that measures different determinants of people's food choices and simultaneously accounts for a variety of factors: health, emotions, price and availability, society and culture, environment and politics, and marketing and advertising.